Tasks Versus Conditions: Two Perspectives on Task Research and Their Implications for Pedagogy. (30th March 2016) - Skehan, Peter
ABSTRACT: This chapter explores the contrast between the effects on second language performance of tasks and task characteristics, on the one hand, and the conditions under which tasks are done, on the other. The first major section explores the evidence on this issue and proposes that the impact of conditions such as pretask planning, task repetition, and posttask activities is greater and more consistent than the impact of tasks and features such as time perspective or number of elements. The second major section explores the theoretical accounts that have been proposed regarding tasks and conditions. It is suggested that deductive accounts have, so far, only had limited success regarding the use of tasks, but that psycholinguistic models of speaking do provide a looser but more useful framework to account for the effects of conditions. It is also suggested that an important difference between tasks and conditions concerns the tension between constraint and flexibility in performance and that the flexibility provided by task conditions is an important component in the more dependable results they have generated. Finally, pedagogic implications are discussed linking task conditions to the methodological choices that are available to teachers.